Consciousness raising tasks for the learning of grammar in high school English language classrooms - Salazar Miranda, Jean Pool (2018)
From the pedagogical mediation of English grammar, many instructors heavily rely on textbooks, but many textbooks promote memorization instead of conscious use of grammar. Based on this premise, this article aims to evaluate the effectiveness of Consciousness Raising Grammar Tasks as a strategy to teach three verb tenses in English. The study followed a mixed method approach with a component of classroom action research, where the researchers taught the simple past, the past continuous, and the present perfect to a group of ninth graders in the Reading and Writing class at the Palmares Bilingual High School, Alajuela, Costa Rica within the tasks studied. The data analyzed consisted of the mean scores of the tasks (pre-post-delayed) and the triangulation of the perspectives of students, cooperating teacher, and the researchers. The results of the mean scores revealed an improvement in all the tenses in the post test and that most scores were retained in the delayed test. Through the triangulation of perspectives, the researchers identified that these tasks were positively assessed and that they encouraged active participation and critical thinking on the part of students. The conclusions pointed to a possible cumulative effect of the implementation of the tasks and to a need for exploring the impact of these tasks on the students’ ability for self-monitoring in more independent practice.